FISHERY, AGE, GROWTH AND MORTALITY ESTIMATES OF TRICHIURUS LEPTURUS LINNAEUS FROM BOMBAY WATERS - Chakraborty, S K (Indian Journal of Fisheries, 2011)
Fishery, age, growth and mortality estimates of Trichiurus lepturus Linnaeus is described in the present communication. During the sixteen year period from 1969 to 1984 the average contribution of ribbon fish to the total marine landings in India was 3.94%. At New Ferry Wharf and Sassoon Docks landing centres of Greater Bombay, ribbon fish contributed 6.44 and 5.92% respectively to the total marine catch during 1980-’86 period. The VBGF parameters in length estimated were L- = 129.7cm, K = 0.50335 (annual) and t^ = +0.0011125 years. This species grows to 51.2, 82.5,101.0 cm at the end of first, second and third year of its life respectively. The average total mortality ’Z’ for the 1979 - ’80 to 1981-’82 period was estimated as 1.96, natural mortality (M) as 1.05 and fishing mortality (F) as 0.91. The exploitation rate (U) and exploitation ratio (E) was estimated as 039 and 0.46 respectively